Determination of Compliance Behavior of BP Jamsostek Membership Contribution Payments for Vulnerable Workers Participating in the Gn Lingkaran Program - Habieb Pahlevi (Contemporary Journal of Applied Sciences, 2024)
Compliance behavior refers to an action or change in a person's attitude to accept, adhere to, and implement applicable rules/regulations with full awareness and without coercion. Compliance behavior in society, in relation to BP Jamsostek, is demonstrated by voluntarily becoming participants and paying contributions on time every month. This behavior benefits not only individuals but also the Indonesian people as a whole, as BP Jamsostek operates under the principle of mutual cooperation. The research method employed is Structural Equation Modeling (SEM), with respondents being all Vulnerable Workers who have been or are currently participants of BP Jamsostek. The sampling technique used is simple random sampling. The research findings indicate that Perceived Usefulness directly influences Attitude and Perceived Value. Additionally, Perceived Usefulness, Subjective Norms, Behavioral Control, and Perceived Value directly affect Behavioral Intention, whereas Attitude does not directly influence Behavioral Intention. Indirectly, Perceived Usefulness through Attitude does not influence Behavioral Intention, but Perceived Usefulness through Perceived Value does influence Behavioral Intention. The implication of these findings is that BP Jamsostek needs to enhance communication regarding the benefits of participation, as Vulnerable Workers perceive the benefits they receive to be indirect, unlike BPJS Kesehatan.